Role of Matrix Metalloproteinase in the Progression of Heart Failure: A Narrative Review - Sidhi Laksono; Budhi Setianto; Reynaldo Halomoan (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2021)
Heart failure (HF) is a cardiovascular disease with a complex pathological pathway and influenced by many factors. Such a complex pathological mechanism would impair cardiac function and structural stability. One that plays a role in maintaining the function and structure of the heart is the extracellular matrix (ECM), and disruption in the extracellular matrix has a role in causing cardiac dysfunction. ECM regulation is associated with matrix metalloproteinase (MMP). Overexpression of matrix metalloproteinases can lead to ECM degradation process which leads to cardiac remodelling. The role of MMP in heart failure is also related to the increased inflammatory response, which is one of the pathways for progression of heart failure. The close association of MMP with the development of heart failure makes MMP a potential biological marker. This article aims was to understand the role of MMP and its mechanisms in cardiac remodelling pathways leading to heart failure. This narrative review suggests that overexpression of MMP can lead to heart failure. Inflammation is one of the factors triggering the expression of MMP. Inflammation will increase the release of pro-inflammatory cytokines, thereby triggering MMP expression. MMP expression imbalance can damage collagen tissue through ECM degradation and damage the structure and function of the heart. MMP can also be used as a biological marker in heart failure cases. The application of MMP as a biological marker can be used to assess the degree of disease severity as well as a predictor of heart failure. In conclusion, MMP has an important role in the development process of heart failure and can be a biological marker in cases of heart failure.